Association of other Autoimmune Diseases in Vitiligo Patients (Community Based Medical Journal, 2013)
A cross sectional study of thirty eight vitiligo patients attending at the outpatients was conducted. The result revealed generalized presentation in 53.6% cases followed by focal presentation, acro-facial and segmented presentation which were 26.3% cases, 15.8%cases and 5.3% cases. Progressive type was found in majority of cases which were 71.1% cases followed by stable case which was 39.9% cases and positive family history was found in 36.8% cases in our study. Among 38 vitiligo patients highest number of associated autoimmune disease was the thyroid abnormalities of which hypothyroidism was 15.8% and hyperthyroidism was 7.9% cases respectively. Diabetes mellitus was found in 2.6% cases, Addisons disease and SLE were found in 2.6%case each. No autoimmune disease was found in the rest 68.5% cases. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16700 Community Based Medical Journal 2013 July: Vol.02 No 02: 57-61